Contemporary Perspectives on Environmental Enforcement - Nurse, Angus (International journal of offender therapy and comparative criminology, 2022)
Green criminology allows for the study of environmental and criminal laws, environmental criminality which includes widespread environmental harm, and the abuse and exploitation of nonhuman animals. Yet many environmental crimes are not the core focus of criminal justice systems or public concern about crime and safety despite having the potential to cause far wider social harm and a large number of deaths. Instead much environmental enforcement is regulatory or administrative in nature, particularly in respect of corporate environmental wrongdoing, which is often categorized as accidental wrongdoing, largely considered to be the fault of ?rogue? employees or the unintended consequences of governance failures. Unlike traditional street and property crimes, environmental crimes (and environmental harms) frequently have long-lasting and irreversible effects. This raises questions about the effectiveness of justice systems in dealing with environmental offenders and the damage they cause. This paper explores the effectiveness of contemporary environmental enforcement mechanisms. In particular, the paper explores the extent to which they such mechanism are equipped to deal with corporate environmental offending which in many cases is a consequence of the operation of neoliberal markets. This paper examines whether the drive for profits and anthropocentric attitudes toward the environment and exploitation of natural resources create a situation where corporate environmental crime is a foreseeable and even natural/inevitable consequence. Where that is the case and where corporations have the resources to continue paying fines and the expertise to navigate regulatory justice systems, an alternative to the law enforcement ?detection apprehension and punishment? approach might be required.